2011
DOI: 10.1007/s10238-011-0131-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of subchondral bone quality by alendronate administration for the reduction of cartilage degeneration in the early phase of experimental osteoarthritis

Abstract: To evaluate the effects of alendronate (ALN) on the subchondral bone quality and cartilage degeneration in the early phase of experimental model of osteoarthritis after anterior cruciate ligament transaction (ACLT). Thirty male adult healthy Japanese white rabbits after right ACLT or sham operation were divided into three groups (n = 10 per group): Sham; ACLT + ALN [after ACLT, the rabbits were treated with ALN daily starting from 4 days after surgery (10 μg/kg/d subcutaneously)]; and ACLT + NS group (after AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 33 publications
4
36
1
5
Order By: Relevance
“…Early in the pathogenesis of OA, prior to the development of sclerosis, there is a period of periarticular osteopenia [60] and a significant reduction in bone mineral density was reported in patients with mild OA when it was compared to healthy ones [61]. These effects on bone were expected in the animals treated with risedronate, a potent aminobisphophonate, which showed its effectiveness in conserving the periarticular bone [62]. In the same way, high molecular weight hyaluronic acid was shown to promote human osteoblast bone matrix protein expression in vitro [63] and bone formation in vivo [64] as well as to reduce bone resorption, but no study on this effect of diacerein on bones, to the best of the authors’ knowledge, has been published yet.…”
Section: Discussionmentioning
confidence: 99%
“…Early in the pathogenesis of OA, prior to the development of sclerosis, there is a period of periarticular osteopenia [60] and a significant reduction in bone mineral density was reported in patients with mild OA when it was compared to healthy ones [61]. These effects on bone were expected in the animals treated with risedronate, a potent aminobisphophonate, which showed its effectiveness in conserving the periarticular bone [62]. In the same way, high molecular weight hyaluronic acid was shown to promote human osteoblast bone matrix protein expression in vitro [63] and bone formation in vivo [64] as well as to reduce bone resorption, but no study on this effect of diacerein on bones, to the best of the authors’ knowledge, has been published yet.…”
Section: Discussionmentioning
confidence: 99%
“…ALN has shown the ability to retain subchondral and periarticular bone following initiation of OA in multiple animal models [10-16]. Importantly, ALN has also exhibited chondroprotective effects [10,12,13,16], and has exhibited the ability to reduce the formation of osteophytes [10,12,15]. However, there is some inconsistency in the reported benefits of ALN for preventing OA; some studies have found no chondroprotective effect in animals treated with ALN [14], or even a negative effect on articular cartilage [11].…”
Section: Introductionmentioning
confidence: 99%
“…Another notable shortcoming in the prior studies is the lack of a non-invasive method of joint injury to initiate PTOA. Prior studies typically used invasive surgical means to initiate PTOA, including anterior cruciate ligament (ACL) transection [10,12,13,16] or medial meniscectomy [12,15]. However, these methods may complicate the outcomes of the study due to unintended effects from the invasive surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…These positive alendronate effects were associated to an increase of OPG/RANKL ratio in both subchondral bone and cartilage and blocking of MMP-13 and MMP-9 expression in articular cartilage and the interface between articular cartilage and subchondral bone [21]. Likewise, cartilage protection associated with the improvement of subchondral bone quality through reduction of subchondral bone resorption was described in the early phase of the ACLT-induced OA in rabbits following alendronate administration [22]. In this experimental model, alendronate suppressed the expression of MMP-13, IL-1β, type-X collagen, vascular endothelial growth factor, and receptor activator of nuclear factor-κB ligand in OA cartilage [23].…”
Section: Animal Studiesmentioning
confidence: 87%